Distribution pattern and activity of mitochondria during oocyte growth and maturation in the ascidian Styela plicata*. Issue 4 (November 2014) - Bezzaouia, Amina; Gallo, Alessandra; Silvestre, Francesco; Tekaya, Saïda; Tosti, Elisabetta
Summary The process of oocyte maturation is underlined by a redistribution of cellular organelles, among which mitochondria play a functional role for the acquisition of fertilization and developmental competence. In this paper, we applied electron and confocal microscopy by using DIOC6 and JC-1 stain to evaluate mitochondria distribution pattern and activity during different stages of oocyte growth in the ascidian Styela plicata. Three categories of oocytes at the germinal vesicle stage underlying the vitellogenic process were characterized on the basis of size, pigmentation and accessory cells. Mitochondria were spread throughout the cytoplasm at the smallest oocyte stage and gradually migrated to the periphery of the subcortical cytoplasm at the intermediate stage. At the fully grown oocyte stage, mitochondria were aggregated in the subcortical cytoplasm. This pattern of polarized mitochondria distribution correlates significantly with an increase in mitochondria potential and activity. In this paper we discuss the relationship of mitochondria to the acquisition of oocyte developmental competence.